Virus disinfection for biotechnology applications: Different effectiveness on surface versus in suspension. (March 2020) - Kindermann, Johanna; Karbiener, Michael; Leydold, Sandra M.; Knotzer, Simone; Modrof, Jens; Kreil, Thomas R.
Abstract: Virus contamination events in cell culture-based biotechnology processes have occurred and have had a dramatic impact on the supply of life-saving drugs, and thus on the wellbeing of patients. Cleanup requires effective and robust virucidal decontamination procedures for both the liquid reactor content before discharge, as well as facility surfaces to prevent recurrence. Beyond rare contamination events, it is important to implement virucidal disinfection for change-over procedures as effective preventive measure in routine biomanufacturing. Knowledge of the virus inactivation capacity of commonly used disinfectants is therefore important. However, available virus inactivation data often refer to studies performed in suspension only, and not, as often more relevant, to virus inactivation on surfaces. In this study three liquid disinfectants, based on sodium hypochlorite, glutaraldehyde, or hydrogen peroxide/peroxyacetic acid, as well as one gaseous hydrogen peroxide-based disinfectant were investigated for inactivation of lipid enveloped and non-lipid enveloped model viruses, using suspension (for the liquid disinfectants) and carrier assay designs for their virucidal efficacy on surface. The results of these side-by-side investigations demonstrate that depending on the type of application, i.e. routine surface disinfection or decontamination of e.g. a contaminated bioreactor content, the most effective choice of disinfectant may be remarkably different.